Future 'New Old' perception on colour preference of product design / Nurazlina Jamalludin and Mohamat Najib Mat Noor - Jamalludin, Nurazlina; Mat Noor, Mohamat Najib (2019)
The growth of the older generation is estimated to be increase from 2010 to 2030 specifically in Malaysia. Particularly with the rise of this generation, consumerism aspect in product designs development will be affected in order to cater this market. Within this challenge, the product appearance is estimated to evolve according to the perception and choice of older generation in their daily lives. This research studies the consumers' perception on the product appearance that is normally used in everyday life. In this paper the emphasis is given on the colour spect of the daily used product that has been assessed. Furthermore, the highlighted users are from aged between 45-65 years known as future 'New Old' and the research was explored through survey as an instrument. The descriptive analysis was performed to analyse the respondents' perception towards colour preferences. The findings show that warm colour is slightly importance and preferable colour in choosing a product for future 'New Old'. In addition, suggestions are made as a way forward to produce a product using the preference colours in conjunction to make the product look more attractive and essentially fit their age and follow the future trend. With the availability of this study, researchers or designers thereby can produce a quality and better product design requirement that meet the consumer needs.